Caregiver satisfaction with a specialist inpatient unit: are we getting it right?. (1st September 2017) - Onwumere, Juliana; Bonomo, Matteo; Yuen, Valeria; McGourty, Alison; Shergill, Sukhwinder; Gaughran, Fiona
Aim: Consumer satisfaction is an increasingly important component in determining the delivery of high quality healthcare, particularly for mental health services. However, the perspectives of the relatives (informal carers) of patient groups remains largely overlooked but is invaluable in mental health settings treating non-capacitous patient groups. The aim of the current study was to assess carer feedback on their experience of an inpatient service for people with long-term psychotic disorders.Method: At discharge from the inpatient service, all informal carers of patients were routinely invited to complete a service feedback questionnaire. This included questions asking their assessment of service setting including cleanliness, communication with staff, quality of service provision, and degree to which they felt involved.Results: Data from 61 carers (62% of eligible sample) collected over a five-year period are presented. Overall, these indicated a high level of satisfaction with the service, a willingness to recommend the service to others, and a positive view of having the opportunity for involvement and inclusion in their relatives' care. Qualitative feedback detailing less helpful aspects of the service highlighted communication issues with staff, being made to wait for things such as gaining entry to the unit, and limited visiting spaces for families.Clinical implications: Carers have an invaluable role to play in optimising patient outcomes in psychosis. Here, we demonstrate that not only is it feasible to elicit their feedback on service provision but also that this provides useful information for assessing service quality and identifying areas in need of improvement.